2000
DOI: 10.1021/es991246a
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Modeling of the Humic Colloid-Borne Americium(III) Migration by a Kinetic Approach

Abstract: The humic colloid-borne Am(III) migration is investigated by laboratory experiment. As the reactions controlling the Am(III) migration are found to be not in equilibrium, the experimental results are interpreted by a kinetic model, i.e., the Kinetically Controlled Availability Model (KICAM). Model parameters determined by fitting experimental data in one groundwater sand system are applied (i) to describe the Am(III) sorption and migration behavior in three other groundwater sand systems with lower humic collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Its relatively large portion in the strong hydrophobic fraction (SPE cartridge) is consistent with the association of 241 Am with NOM in other studies (Artinger et al, 1998;Schuessler et al, 2000;Cooper et al, 1995, to name a few). Our sample somewhat contrasts the findings of Cooper et al (1995), because their chromatographic separation suggested that 241 Am was associated with the smaller-sized NOM.…”
Section: Americium-241supporting
confidence: 88%
See 1 more Smart Citation
“…Its relatively large portion in the strong hydrophobic fraction (SPE cartridge) is consistent with the association of 241 Am with NOM in other studies (Artinger et al, 1998;Schuessler et al, 2000;Cooper et al, 1995, to name a few). Our sample somewhat contrasts the findings of Cooper et al (1995), because their chromatographic separation suggested that 241 Am was associated with the smaller-sized NOM.…”
Section: Americium-241supporting
confidence: 88%
“…Our sample somewhat contrasts the findings of Cooper et al (1995), because their chromatographic separation suggested that 241 Am was associated with the smaller-sized NOM. The work at the Gorleben site (Artinger et al, 1998;Schuessler et al, 2000) is particularly significant, because the authors deal with the kinetics of association/dissociation of Am with NOM. Their experiments extended over several thousands of hours (months), and they obtained both kinetic and equilibrium constants, with more than one binding site.…”
Section: Americium-241mentioning
confidence: 99%
“…The additivity of the models for mixed illite/NOM systems will now be tested. However, the two models rely on equilibrium conditions being present in the experimental systems, and radionuclide interactions in quasi-natural systems containing dissolved NOM are known to exhibit slow kinetic rates (e.g., [30][31][32]). Thus, it must be verified whether the measured Eu solid-liquid distribution is truly for equilibrium conditions.…”
Section: Sorption Of Europium In Combined Illite/nom (Ternary) Systemsmentioning
confidence: 99%
“…Another factor that could affect the sorption of the radionuclides concerned and of weighable amounts of uranium and stable Eu is formation of their hydrolyzed species at high pH typical of Yenisei river water (pH > 7.5) [21,22]. As a result, radionuclide-containing multicomponent polymeric hydroxo complexes…”
Section: Sorption Kinetics Of 241 Am and 242 Pu Tracers And Weighablementioning
confidence: 99%